2015
DOI: 10.1371/journal.pone.0118332
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation-Related Reduced Somatostatin Production Promotes Uncontrolled Cell Proliferation in Colorectal Cancer

Abstract: BackgroundSomatostatin (SST) has anti-proliferative and pro-apoptotic effects. Our aims were to analyze and compare the SST expression during normal aging and colorectal carcinogenesis at mRNA and protein levels. Furthermore, we tested the methylation status of SST in biopsy samples, and the cell growth inhibitory effect of the SST analogue octreotide in human colorectal adenocarcinoma cell line.MethodsColonic samples were collected from healthy children (n1 = 6), healthy adults (n2 = 41) and colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 65 publications
2
33
0
Order By: Relevance
“…SST is a neuropeptide that has been shown in models of breast cancer to both inhibit growth factors and hormones known to promote tumour growth, as well as prevent receptor signalling that can trigger apoptosis [ 12 ]. Additionally, the role of epigenetic silencing as a means of suppressing SST expression in tumour cells has previously been suggested by the observed hypermethylation of the SST promoter CpG island in multiple tumour types including cervical cancer [ 13 ], colorectal cancer [ 14 , 15 ], gastric cancer [ 16 ], and renal cell carcinoma [ 17 ]. VGLL4 has also been identified as a potential tumour suppressor gene across multiple tumour types including breast cancer [ 18 ], gastric cancer [ 19 ], and lung cancer [ 20 ] and overexpression of VGLL4 has been found to suppress breast tumour growth in vivo [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…SST is a neuropeptide that has been shown in models of breast cancer to both inhibit growth factors and hormones known to promote tumour growth, as well as prevent receptor signalling that can trigger apoptosis [ 12 ]. Additionally, the role of epigenetic silencing as a means of suppressing SST expression in tumour cells has previously been suggested by the observed hypermethylation of the SST promoter CpG island in multiple tumour types including cervical cancer [ 13 ], colorectal cancer [ 14 , 15 ], gastric cancer [ 16 ], and renal cell carcinoma [ 17 ]. VGLL4 has also been identified as a potential tumour suppressor gene across multiple tumour types including breast cancer [ 18 ], gastric cancer [ 19 ], and lung cancer [ 20 ] and overexpression of VGLL4 has been found to suppress breast tumour growth in vivo [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin, encoded by the SST gene, is a peptide hormone secreted by parts of the CNS that affect neurotransmission and cell proliferation (36,37). A hypermethylation-associated decrease in somatostatin expression was reported to be important for uncontrolled proliferation of colorectal cancer and gastric cancer (3840).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the genes evaluated in this study were reported to have a (putative) tumor suppressive function (i.e., C13orf18 [24], EPB41L3 [2529], PRDM14 [30], SOX1 [31,32], SST [33,34], ZIC1 [35,36], and ZSCAN1 [37,38]). The remaining genes with a currently unknown function await further study.…”
Section: Discussionmentioning
confidence: 99%